Boards, ownership structure, and involuntary delisting from the New York Stock Exchange - Charitou, Andreas; Louca, Christodoulos; Vafeas, Nikos (My University, 2007)
This study examines whether the likelihood of becoming involuntarily delisted from NYSE is associated with a firm's board of directors and ownership characteristics. To this end we compare 161 firms that were delisted from NYSE between 1998 and 2004 to a set of industry and size-matched control firms. Consistent with our expectations, we find that the likelihood of delisting is related to a firm's governance characteristics. Our results on the importance of the board of directors are new to this setting and add to a large body of evidence linking corporate boards and ownership characteristics to corporate performance.
Keywords: Board of directors; Delisting; NYSE